(untitled) (Journal of NELTA, 2018)
Adjectives occupy an important space in Basic level school curriculum in Nepal. Teaching three forms of adjectives (base, comparative and superlatives) can be challenging for teachers and boring for students if an appropriate technique or activity is not used. Here is an interesting and fun game for teaching comparison adjectives to beginners. Journal of NELTA , Vol. 22, No. 1-2, 2017 December, Page: 140-143